2010
DOI: 10.1016/j.mcn.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia in rats impairs the cholinergic system and leads to memory deficits

Abstract: Alzheimer's disease (AD) is a chronic brain disorder characterized by cognitive impairment, cholinergic dysfunction, inflammation, tau and beta-amyloid pathology and vascular damage. Recent studies have shown, that high cholesterol levels are linked to the pathology of AD. The aim of our present work was to study the effects of hypercholesterolemia in adult rats. Five months after 5% cholesterol-enriched diet plasma cholesterol levels and total weight were significantly enhanced compared to controls. Spatial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
142
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 104 publications
11
142
1
2
Order By: Relevance
“…In addition, several lines of evidence have confirmed that hypercholesterolemia affects oxidative stress and Aβ in animal and shows some neuropathological changes similar to those seen in memory disorders [8,57]. Epidemiological studies suggest that high level of cholesterol increases Aβ generation and inhibits α-secretase via activation of both β-and γ-secretases and that hypercholesterolemia increases Aβ levels in the brain [58].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, several lines of evidence have confirmed that hypercholesterolemia affects oxidative stress and Aβ in animal and shows some neuropathological changes similar to those seen in memory disorders [8,57]. Epidemiological studies suggest that high level of cholesterol increases Aβ generation and inhibits α-secretase via activation of both β-and γ-secretases and that hypercholesterolemia increases Aβ levels in the brain [58].…”
Section: Discussionmentioning
confidence: 82%
“…Obesity and hypercholesterolemia and oxidative stress play a pivotal role in the development of learning and memory impairment [4,8,9]. Long-term use of high fat diet or high energy diet could induce obesity and affect serum lipid levels and oxidative stress, which in turn affect learning and memory functions [37,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that diet-induced hypercholesterolemia, or high cholesterol, in male Sprague Dawley rats results in impaired learning and memory, reduced survival of NBM (Nucleus Basalis of Meynert) cholinergic neurons, reduced cortical acetylcholine, elevated inflammatory factors, elevated cortical β-amyloid, tau, and phospho-tau 181 and increased presence of small cortical BBB (blood brain barrier) feedings [13].…”
Section: Discussionmentioning
confidence: 99%
“…Second, apoE4 is associated with elevated levels of plasma cholesterol [4,5]. Third, elevated levels of plasma cholesterol, independent of APOE genotypes, has been linked to the pathogenesis of sporadic AD [6][7][8][9][10], as supported by epidemiology studies [6,9] as well as experimental studies conducted in AβPP transgenic mice [11,12], in guinea pigs [13], in rabbits [14], and in rats [15].…”
Section: Introductionmentioning
confidence: 99%